The collapse of the synodal system (the end of the nineteenth – the beginning of the twentieth century): concepts of modern Orthodox historiography - Савченко, Сергій (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2020)
Purpose of the study. To analyze the works of modern historians, reflecting the intra-church vision of the situation of the Orthodox Church in the Russian Empire from the end of the nineteenth century to 1917. Attention is focused on assessments of the late synodal system, the need to Church renew, Church freedom in the state, the clergy perception of the February Revolution and the new government. The concept of «modern Church / Orthodox historiography» is used in a broad and conditional sense. Itʼs represented by authors of various ideological and canonical directions of the twentieth – early twenty-first century. The research methodology is based on a comparative study of the historiographic concepts mainly of the second half of the 20th century – the beginning of the 21st century. We study the most influential generalizing texts representing the position of various groups in the Russian Orthodox Church, as well as the works of Orthodox historians of emigration, the diaspora, Church dissidents. They have mostly liberal views and assessments of the Church process. The scientific novelty. The novelty of the study is determined by the weakness of the internal Church critical reflection, since the Church history functions within the framework of the apologetic and descriptive paradigm. Modern Church historiography is a specific phenomenon of historical science. Itʼs trying to combine two difficult tasks: religious apologetics and academic research. The article showed the negative aspects of this approach. Findings. The main lack of modern Church historiography is the indifference to non-political aspects of Church history. The potential of historical anthropology, intellectual history, the social history of ideas, and the history of mentality is ignored. As a result, many promising stories fall out of Сhurch historiography. These subjects are successfully investigated by secular historians. Common problem of the Orthodox historiography is thematic limitations, the tendency of the phenomenological «encapsulation» of the Church in the historical process, the conceptual dependence on Orthodox journalism at the turn of the 19th-20th centuries. Also, the weak representativeness of the sources as a result of inattention to local documentary sources.